Composition and biological activities of essential oils from Limnophila geoffrayi Bonati - Jeerayu Thongdon-A (2018)
Essential oils from the dried aerial parts of Limnophila geoffrayi Bonati were obtained by water-distillation. d-Pulegone (27.14%), perillaldehyde (19.13%) and limonene (9.00%) were characterized as the major constituents using gas chromatography-mass spectrometry analysis. The antimicrobial activities of the essential oils and their major components were evaluated against microorganisms encountered normally in contaminated cosmetic products, using the agar- and broth-dilution methods. Their insecticidal activities against the Oriental fruit fly Bactrocera dorsalis (Hendel) were tested using a bioassay with impregnated filter paper. The results showed that the essential oils possessed high antimicrobial activity, with minimum inhibitory concentrations ranging from 0.03 to 0.2% per unit volume (v/v). Strong insecticidal activity as a fumigant was also observed at an oil dose of 5 μl/disc, with a 94% mortality. Perillaldehyde was the most active compound among the main components of these essential oils. © Springer Science+Business Media B.V. 2009.